Utilization of Nanomaterials to Catalyze Chemical Reactions and Enhance Industrial Performance - Abd_Alsada, Zahraa Mohammad; Al-ziyadi, Salah Hassan Abhoul; Wadi, Ameer Abdul Hussein Bahar; Abdulmajeed, Reham Haitham; Hasan, Panar Qasim (American Journal of Biomedicine and Pharmacy, 2025)
Nanomaterials serve as effective catalysts for economically important chemical reactions and offer the potential to enhance industrial performance through sustainable and cost-efficient processes. They comprise metallic, metal oxide, carbon-based, and polymeric nanomaterials, each with unique structural features and properties that affect catalytic activity. Synthesis methods include top-down and bottom-up approaches, as well as green protocols, which influence the resulting nanomaterial characteristics. Comprehensive characterization employs electron microscopy, X-ray diffraction, and spectroscopic techniques to investigate morphology, crystallinity, elemental composition, and surface chemistry . Catalytic properties derive from large surface-to-volume ratios and abundant active sites that enhance interaction with reagents. Applications span organic synthesis, environmental remediation, and energy production, illustrating versatility across the chemical industry. Performance enhancements focus on higher conversion rates, lower costs, and improved sustainability. Despite various benefits, challenges remain concerning scalability, regulatory compliance, and safety, highlighting areas for future research and development.